Analisis Biaya Diferensial dalam Pengambilan Keputusan untuk Menerima atau Menolak Pesanan Khusus: Studi Kasus UMKM Sinomque dan UMKM Boba Kiya-Kiya - Paranti, Desmala; Kurniawati, Dinda Dwi; Pandin, Maria Yovita R; Riyadi, Slamet (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
In making decisions to accept or reject special orders in MSMEs, business owners often face cost considerations. Therefore, the application of differential cost analysis is needed as part of decision making. The right decision will impact profit improvement. This study aims to evaluate the implementation of differential cost analysis in decision making for MSMEs related to special orders. The research method used is qualitative with a case study approach. Data was collected through direct interviews with business owners and documentation. Case studies were conducted on 2 MSMEs. The results show that differential cost analysis can help business owners accurately calculate the profit from accepting special orders.